Peran Guru Dalam Meningkatkan Karakter Peserta Didik di SD pada SMB Mandala Maitreya Pekanbaru - Solin, Solin; Irawati, Irawati (Jurnal Maitreyawira, 2026)
This research aims to explore the teacher's role in fostering students' caring character. The study employs a qualitative method with a descriptive approach, conducted at Mandala Maitreya Buddhist Sunday School in Pekanbaru. Data collection techniques include teacher interviews, observation, and documentation. Data analysis uses the interactive data analysis technique by Miles and Huberman. The findings highlight the pivotal role of teachers in enhancing students' caring character. Teachers at Mandala Maitreya Primary School in Pekanbaru diligently fulfill their roles as mandated by the law, adapted to the school's regulations, and driven by individual creativity. Each teacher tailors their teaching approach to match the students' unique situations and conditions. The research specifically identifies several roles carried out by teachers at Mandala Maitreya Primary School in promoting students' caring character, including being a role model, a supportive friend, and an effective communicator within the school community. Further clarification reveals that teachers play a crucial part in internalizing caring character values through leading by example, demonstrating friendly attitudes, and effective communication. By exemplifying caring behavior, teachers provide tangible instances of how to show concern for others. As friends, they offer valuable support and guidance, fostering caring attitudes. Furthermore, as adept communicators, teachers interact effectively with students, ensuring the clear and understandable transmission of caring character values.